Demographic Factors Associated with Opioid Use Following Laparoscopic or Robotic Hysterectomy [8R]. (May 2018) - Cohen, Michael; Weston, Erica; Raker, Christina; Huang, David; Mathews, Cara
Abstract : INTRODUCTION: The number of opioid-related deaths has quadrupled in the United States since 1999, and the opioid crisis is well-defined. The purpose of this study is to identify demographic predictors of increased inpatient and post-discharge opioid use in order to tailor postoperative opioid dispensation. METHODS: This study is a secondary analysis of a prospective cohort designed to correlate mindfulness with post-operative pain in patients undergoing laparoscopic or robotic hysterectomy by a gynecologic oncologist at a single institution. Inpatient opioid use was measured via chart review and outpatient use via surveys at 1-2 week and 4-6 week post-operative visits and via pharmacy records. Demographic information was measured via chart review and pre-operative surveys. Descriptive statistics and correlation were used to determine associations. RESULTS: Mean age (n=126) was 60.4 (SD 11.66) and mean BMI was 33.6 (SD 9.35). Additionally, 54% of subjects had private insurance, 20% had Medicaid products, and 25.6% had Medicare. 85% of subjects were referred from a private OBGYN office. Younger patients used significantly more opioids inpatient and outpatient based on total milligram morphine equivalents (MME) (p=0.0003 inpatient, p=0.045 outpatient) and total number of doses (p=0.001 inpatient; p=0.048 outpatient). Insurance source trended with post-discharge MMEs used, with Medicaid patients using more, but this correlation was not statistically significant (p=0.13). BMI, race, insurance status, referral source, and comorbidities did not predict post-operative opioid use. CONCLUSION: Older patient use fewer opioids and this population may be a target for smaller postoperative prescriptions to reduce unused opioids. This warrants further study in other populations.